Studi Kecermatan Alat Ukur Roundness Tester Machine Produksi Laboratorium Jurusan Teknik Mesin Universitas Riau Dengan Metode Helix - Shodikin, Shodikin; Prayitno, Adhy; Arief, Dodi Sofyan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
measuring clock or Dial indicators is a comperator device. typically used in industrial activities in particular at product deviation, because it has good accuracy. Precision and accuracy is the closeness to the true value, can be defined as the closeness (cloness) between the values read from the measuring instrument to the true value. The use of measuring devices which have high accuracy and good will generate accurate measurement data and vice versa use measuring devices that are not good or accurate, then the results obtained are not accurate. This study aims to determine the accuracy of measuring instruments by varying the motor speed to the drive dial indicator with helix methods, and large roundness deviation (Roundness Tester Machine). The result showed that the roundness deviation for each speed roundness of the lowest value and the highest at speed 0,040 m / s is: MCC = 0.008 mm to 0.124 mm, MZC = 0.008 mm to 0.122 mm, MIC = 0.006 mm to 0.029 mm, and LSC = 0.005 to 0.085 mm. Then to the speed of 0.046 m / s roundness deviation obtained MCC = 0.007 mm to 0,186 mm, MZC = 0.005 mm to 127 mm, MIC = 0.005 mm to 0.121 mm, LSC = 0.005 mm to 0,113 mm, while the speed of 0.071 m / s roundness deviation obtained for MCC = 0.094 mm to 0.611 mm, MZC = 0.047 mm to 0,153 mm, MIC = 0,050 mm to 0.107 mm, LSC = 0.042 mm to 0.111 mm, the speed of 0,040 m / s is closer to the data than the speed of other mandrel, the effect of instrument error is evident from the table 4:20 on four very large positions are not accurate Measure tool is e (mm) = 0.0830 or e (%) = 42.17, and the roundness deviation at speed of 0,040 m/s by the largest outer circle the minimum is 0.124 mm, the inner circle is 0.122 mm maximum, the minimum of a circle area is 0.122, and for the least squares circle is 0.042 mm. The fourth circle of reference is used, then the circle of least squares best used to determine the roundness deviation results in accordance recommended ISO.          Keywords : deviation, helix method, Roundness Tester Machine, speed variation.